2020
DOI: 10.1038/s41598-020-57932-9
|View full text |Cite
|
Sign up to set email alerts
|

Tannic acid inhibits lipid metabolism and induce ROS in prostate cancer cells

Abstract: Prostate cancer (PCa) cells exploit the aberrant lipid signaling and metabolism as their survival advantage. Also, intracellular storage lipids act as fuel for the PCa proliferation. However, few studies were available that addressed the topic of targeting lipid metabolism in PCa. Here, we assessed the tannic acid (TA) lipid-targeting ability and its capability to induce endoplasmic reticulum (ER) stress by reactive oxygen species (ROS) in PCa cells. TA exhibited dual effects by inhibiting lipogenic signaling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 83 publications
0
32
1
Order By: Relevance
“…Although the present study indicated that TA attenuated ROS, ERS and apoptosis in LPS-induced H9C2 cells, there are discrepancies compared with other papers on different cell types; for example, in a previous study on prostate cancer cells, it was revealed that TA induced apoptosis, particularly by mediating ERS (61). TA also induces apoptosis by mediating ROS (62). The present study did not assess other cell models and therefore it is unclear whether TA can protect numerous cell types from apoptosis.…”
Section: Discussioncontrasting
confidence: 93%
“…Although the present study indicated that TA attenuated ROS, ERS and apoptosis in LPS-induced H9C2 cells, there are discrepancies compared with other papers on different cell types; for example, in a previous study on prostate cancer cells, it was revealed that TA induced apoptosis, particularly by mediating ERS (61). TA also induces apoptosis by mediating ROS (62). The present study did not assess other cell models and therefore it is unclear whether TA can protect numerous cell types from apoptosis.…”
Section: Discussioncontrasting
confidence: 93%
“…The broad cancer chemopreventive activity of various tannins in several animal models has been reviewed by Nepka et al [33]. In addition, recent studies have shown the anticancer efficacy of tannins, particularly tannic acid, against prostate and lung cancers [34,35]. The anticancer potentiality of doum palm extracts could be attributed to the high content of individual polyphenols, such as protocatechuic, p-hydroxybenzoic, chlorogenic, rosmarinic, vanillic, p-coumaric acids, apigenin-7-glucoside, rutin and chrysin.…”
Section: Discussionmentioning
confidence: 99%
“…Tannins (commonly referred to as tannic acids, TA) are a class of polyphenolic compounds that are found in a variety of plant-based foods, especially berries, red wine, coffee, nuts and beans. TA is a powerful antioxidant, and therefore exhibits various pharmacological properties such as anti-toxic, anticancer, antiallergic, antiviral and antibacterial abilities [3][4][5][6]. It is thought that TA could protect leaves against insects by deterrence and/or toxicity and induce reactive oxygen species (ROS) development in prostate cancer cells by inhibiting lipid metabolism [3,7].…”
Section: Introductionmentioning
confidence: 99%